2023
DOI: 10.1097/mnh.0000000000000923
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as a therapeutic intervention in chronic kidney disease: are we nearly there yet?

Ellen M. Castle,
Roseanne E. Billany,
Courtney J. Lightfoot
et al.

Abstract: Purpose of review The opportunity to review the more recent evidence for prescribing exercise-based physical rehabilitation for people living with chronic kidney disease (CKD) is timely. There has been a recent global focus evaluating how physical activity interventions might improve health-related quality of life and outcomes for people living with chronic health conditions in a post-COVID era. There is finally a long overdue commitment from the kidney research and clinical community to deliver pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A position statement by the Canadian Society of Transplantation and the Canadian Network for Rehabilitation and Exercise for Solid Organ Transplant Optimal Recovery (CAN-RESTORE) suggested that programs should consist of aerobic training or combined aerobic plus resistance training [1]. Self-management interventions with exercise behaviors, cycling, and other exercise-based interventions was suggested for kidney transplant candidates in a recent narrative review [29]. A systematic review in heart transplant candidates found that high-intensity interval training is generally superior or similar to other exercise training [30].…”
Section: What Are the Optimal Training Characteristics Of Exercise Tr...mentioning
confidence: 99%
See 1 more Smart Citation
“…A position statement by the Canadian Society of Transplantation and the Canadian Network for Rehabilitation and Exercise for Solid Organ Transplant Optimal Recovery (CAN-RESTORE) suggested that programs should consist of aerobic training or combined aerobic plus resistance training [1]. Self-management interventions with exercise behaviors, cycling, and other exercise-based interventions was suggested for kidney transplant candidates in a recent narrative review [29]. A systematic review in heart transplant candidates found that high-intensity interval training is generally superior or similar to other exercise training [30].…”
Section: What Are the Optimal Training Characteristics Of Exercise Tr...mentioning
confidence: 99%
“…Most recent trials have used an outpatient program [9 ▪ ], a home-based program [5 ▪ ], and inpatient intervention [18 ▪ ]. Virtual or telerehabilitation programs have become more frequent since the pandemic and offer ways to deliver interventions with lower cost, but more evidence is needed to determine their efficacy compared to the more traditional methods [1,29].…”
Section: What Are the Optimal Training Characteristics Of Exercise Tr...mentioning
confidence: 99%
“…It revolves around implementing specific lifestyle changes and typically consists of physical exercise training programs, dietary management, and psychosocial interventions. 1 Prehabilitation is now gradually considered to be an essential part of the enhanced recovery pathway for those receiving kidney transplantation. 2 A recently published multi-center clinical trial from the UK by Greenwood and colleagues 3 concluded positive findings on evaluating the effects of a digital health intervention (Kidney BEAM) to enhance physical activity in people with CKD including transplant waitlist patients.…”
mentioning
confidence: 99%
“…Outside of the myriad of medical management modalities that may improve survival and quality of life outcomes in CKD, self-management interventions with a focus on improving physical activity and exercise behaviors has gained tremendous acknowledgement in recent years as a strategy to improve patient outcomes. 1 Prehabilitation is a recent concept that aims to optimize the patient's overall fitness before a major surgical procedure to promote recovery and outcomes overall. It revolves around implementing specific lifestyle changes and typically consists of physical exercise training programs, dietary management, and psychosocial interventions.…”
mentioning
confidence: 99%
See 1 more Smart Citation